The Perfect Storm: A Case of Non-Uremic Calciphylaxis - Manuel Martins Barbosa; Elsa Araújo; Marta Matos Pereira; Tiago Mendes (European Journal of Case Reports in Internal Medicine, 2019)
Calciphylaxis is a severe condition associated with chronic kidney disease. We describe a rare case of non-uremic calciphylaxis in a 79-year-old woman with prosthetic aortic and mitral valves, chronic kidney disease and anaemia, who presented with painful skin lesions on her left leg. She was taking warfarin, calcium and iron supplements, and had been recently diagnosed with oligoarthritis and started on prednisolone, all factors associated with calciphylaxis. Despite treatment, the lesions rapidly progressed to large ulceration and sepsis, and pain management was challenging. Calciphylaxis was confirmed following a second skin biopsy but the patient died from septic shock and multi-organ failure. This case highlights the challenges associated with the diagnosis and treatment of calciphylaxis despite a high level of suspicion.